Shell Lip Thickness Is the Most Reliable Proxy to Sexual Maturity in Queen Conch (Lobatus gigas) of Port Honduras Marine Reserve, Belize; Informing Management to Reduce the Risk of Growth Overfishing - Foley, James R.; Takahashi, Miwa (Frontiers in Marine Science, 2017)
Queen conch (Lobatus gigas) is an important food source and export product for Belize, where extraction is regulated by shell length (SL) and market clean weight (MCW) limits. However, lip thickness (LT) limits are used to manage juvenile mortality and reduce risk of growth overfishing in other countries. Empirical studies suggest relationships between LT and sexual maturity vary spatially and need to be determined locally. This study was conducted to determine the most reliable, easily measurable proxy indicator(s) of maturity and associated target size limits in L. gigas that can effectively restrict harvest of juveniles. Morphological measures (SL, LT, lip width, unprocessed meat weight, MCW, operculum dimensions), gonadosomatic index (GSI) and histological evaluations were recorded from L. gigas collected in PHMR before, during, and after the L. gigas closed season. Upon determining Period 2 (during closed season) as the peak reproductive period, relationships between these variables in Period 2 were examined. No relationship was found in males between SL and maturity, and was weak in females, whereas there were significant curvilinear relationships between LT and GSI for both sexes, suggesting urgent need to base size limits on LT not SL. LT at which 50% of the population was mature (LT50) was 15.51mm for females and 12.33mm for males, therefore a 16mm LT limit is recommended. MCW of female L. gigas was also significantly related to GSI, indicating MCW may be an appropriate management tool in conjunction with LT as it can be measured at landing sites whereas shells are usually discarded at sea. However MCW at which 50% of females were mature (MCW50) was 199g and many individuals exceeding LT50 had MCW less than 199g, suggesting the current 85g MCW limit is too low to protect juveniles yet 199g MCW limit would be too high to substitute the recommended LT limit at landing sites. To minimize short-term impacts yet maximize long-term benefits to fishers’ livelihoods, multi-stage adaptive management is recommended that integrates initial catch reductions, followed by introduction of size limits of 16mm LT, and 150g MCW. Adjustable LT and MCW limits determined by fishery simulation could later be introduced.